A study on the impact of perceived characteristics on purchase intention towards collaboration products between foreign brands and China Chic IPs - Xiantong Cheng; Chanwook Park (Global Business & Finance Review (GBFR), 2023)
Purpose: In recent years, with the continuous development of the China Chic economy, an increasing number of foreign brands have partnered with China Chic intellectual property (IP) to introduce collaborative products. Although collaboration products between foreign brands and China Chic IPs have been consistently introduced, there is still a limited amount of research focusing on these products. This empirical study aims to investigate the factors that influence consumers' attitudes and purchase intentions towards foreign brands and China Chic IPs collaboration products. Design/methodology/approach: This study is based on the conceptual model of factors that determine behavioral intentions to buy co-branded products constructed by Helmig et al. (2007) to verify the effects of perceived brand localness, perceived product innovativeness, perceived fit, and perceived psychological distance on consumer attitudes towards the foreign brand - China Chic IP collaboration products. This study is based on Helmig et al.'s (2007) conceptual model, which examines the factors that determine consumers' behavioral intention to purchase co-branded products. Combined with the research context this study verifies the effects of perceived brand localness, perceived product innovativeness, perceived fit and perceived psychological distance on consumer attitudes towards foreign brands and China Chic IPs collaboration products are examined and verified. The relationships among these variables were assessed through the Structural Equation Model and the SPSS macro process model. Findings: The results indicate that consumer attitudes are positively influenced by perceived product innovativeness and perceived brand localness. On the other hand, perceived psychological distance has a negative impact on attitudes. However, the impact of perceived fit on attitudes has not been conclusively determined. Furthermore, consumer ethnocentrism moderates the relationship between perceived brand localness and attitudes, displaying a negative effect. Lastly, the analysis reveals a positive association between attitudes and purchase intentions for foreign brands and China Chic IPs collaboration products. Research limitations/implications: This study demonstrates that the marketing strategy of collaborating with China Chic IP has a positive impact on Chinese consumers' attitudes towards such collaboration products and their willingness to make purchases. This collaborative strategy serves as a catalyst for stimulating consumers' buying behavior and enhancing the market presence of foreign brands in China. However, this study does have limitations, including the absence of a specific focus on a particular product category and not including variables related to consumers' attitudes towards foreign brands and the country of origin. Originality/value: This study contributes to the research of brand and cultural collaboration strategies. From a marketing perspective, it provides insights on how foreign brands can enhance their collaboration strategy with China Chic IPs in a more systematic and efficient manner.
Keywords: 650; China Chic IPs; collaboration products; perceived brand localness; perceived product innovativeness; perceived psychological distance